An Investigation on Dynamic Response of Collision by Multiple Projectiles Towards Multi-Layer Al2024 T3 Aluminium Plate - Mohd Yassin, Muhammad Haziq; Ibrahim, Mohd Norihan (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Multilayer structure has been widely used in many engineering applications in order to increase durability, performance and safety of its structure. Numerical investigations were carried out on 15 mm thick multilayer aluminium Al 2024 T3 target plates impacted by multiple hemispherical and blunt nose shape of projectiles with a diameter of 10 mm. Three-dimensional numerical simulations were carried out using IMPACT finite element code. The present studies are concerned about the failure process of a deformable multilayer aluminium target plate perforated by multiple projectiles of hemispherical and blunt nose shape as a rigid body. The failure modes of projectiles with different nose shapes have been compared and analysed. The research covered several perforated multilayer aluminium Al 2024 T3 plate failure mode profiles based on impact velocity levels ranging from 20 m/s to 100 m/s. During the perforation by multiple blunt nose shape projectiles, no plugging formation occurs. The petals formation of blunt nose shape of projectile is almost the same as hemispherical nose shape of projectiles at velocities of 20 m/s and 60 m/s. The petal formation size grows larger as the impact velocity increases especially for hemispherical nose shape projectiles. The obvious petal formation size increase can be seen at a velocity of 100 m/s due to an increase in impact velocity. The petal formation size, bulge formation and hole enlargement increase as the impact velocity increases.